Characterization of electrically stressed power device metallization using nano-CT imaging. (August 2022) - Mueller, Dominik; Fella, Christian; Altmann, Frank; Graetz, Jonas; Balles, Andreas; Ring, Matt; Gambino, Jeff
Abstract: Power devices for automotive products are exposed to higher temperatures, currents, and voltages than common semiconductors. These devices are subject to large variations in the nominal power supply voltage. Power-Temperature Cycling (PTC) is an important reliability stress for power semiconductor devices, which addresses these specific load scenarios. It is known that PTC fails especially occur in the metallization of these power devices. Recent nano-CT imaging methods provide high-resolution 3D measurements on the relevant size scale suitable to spatially analyze these faults in detail. In this work, we demonstrate the suitability of the investigation method based on the study of various via-chain test structures previously stressed in the PTC and visually show the various defects that occurred in the process. Highlights: Laboratory based nano-CT analysis for the investigation of defects and faults in power electronics Power-Temperature Cycling (PTC) is an important reliability stress for power semiconductor devices 3D analysis and visualization of the various defects that have occurred PTC test failure of via-chain structures often happens in the metallization of the structures Examination with 150 nm resolution in 3D by computed tomography